1991
DOI: 10.2166/wst.1991.0564
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Microorganisms Immobilized with Magnetic Particles for Sewage and Wastewater Treatment

Abstract: A novel method for sewage and wastewater treatment using microorganisms immobilized with magnetic particles was developed with a proposal of the treatment process. This process has the characteristic of having microorganisms in effluent recovered magnetically. Batch and continuous experiments for phenol removal were carried out using microorganisms immobilized with ferromagnetic particles after cultivation in the presence of phenol. In the continuous experiment, almost 100% of phenol in feed water was removed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 0 publications
0
13
0
2
Order By: Relevance
“…Studies have demonstrated that using MW for irrigation can improve water productivity. In addition, MW is reportedly effective at preventing and removing scale deposits in pipes and water containing structures [9,[29][30][31][32][33][34][35][36][37][38][39].…”
Section: Magnetic Water Treatment In Agriculturementioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated that using MW for irrigation can improve water productivity. In addition, MW is reportedly effective at preventing and removing scale deposits in pipes and water containing structures [9,[29][30][31][32][33][34][35][36][37][38][39].…”
Section: Magnetic Water Treatment In Agriculturementioning
confidence: 99%
“…Safety, compatibility and simplicity, environmentally friendliness, low operating cost and not proven harmful effects are the main advantages of EMFs in these fields [6,16,17,32,35,[40][41][42][43][44][45]. In addition to the antimicrobial and antibacterial effects of EMFs on wastewater treatment, these fields have different characteristics which can be used to enhance a WWT process: modifying the physical and chemical properties of water molecules and other elements, precipitating sludge, removing phosphorus and organic compounds from solutions.…”
Section: Magnetic Wastewater Treatmentmentioning
confidence: 99%
“…The main advantages in the use of immobilized cells in comparison with suspended ones include the retention in the reactor of higher concentrations of micro-organisms, protection of cells against toxic substances and prevention of suspended bacterial biomass in the effluent. Moreover, immobilization of microbial cells provides, in general, high degradation efficiency and good operational stability (Ozaki et al 1991).…”
Section: Resultsmentioning
confidence: 99%
“…No campo do tratamento de águas residuárias, existem estudos da influência da aplicação de campo magnético no processo de lodo ativado (SAKAI et al, 1991;HATTORI et al, 2001;2002) e na biodegradação de fenol (OSAKI et al, 1991;RAJA RAO et al, 1997). Nesses estudos, os resultados avaliam a influência do campo magnético sobre o crescimento da biomassa, a viabilidade celular, a velocidade de conversão do substrato, a velocidade de produção etc., para diferentes condições de processo relacionadas à concentração celular e de substrato, intensidade de campo magnético e a forma de contato entre o campo magnético e o meio líquido.…”
Section: Introductionunclassified